Fairy wings - Baker, E. D. (New York : Bloomsbury, 2012)
When Tamisin discovers that she is half fairy, she decides to find out more answers directly from the fairies themselves, including her mother, the fairy queen.
Formerly titled: Wings.
Booklist
Bulletin (Center for Children's books)
Horn Book
Booklist, May 2008
Bulletin (Center for Children's books), June 2008
Keywords: Fairies -- Juvenile fiction; Fairies -- Fiction; Fairies -- Fiction